2005
DOI: 10.1111/j.1365-2141.2005.05625.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil therapy in patients with sickle cell disease and pulmonary hypertension

Abstract: SummaryPulmonary hypertension is a frequent complication of sickle cell disease that is associated with haemolysis, impaired nitric oxide bioavailability and high mortality. We sought to evaluate the safety and efficacy of selective pulmonary vasodilators and antiproliferative agents in this at‐risk population. After optimising sickle cell disease therapy to stabilise haemoglobin and fetal haemoglobin levels, we evaluated the safety and efficacy of sildenafil in 12 patients with sickle cell disease and pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(137 citation statements)
references
References 29 publications
5
127
0
5
Order By: Relevance
“…on April 3, 2019. by guest www.bloodjournal.org From prevented or minimized the development of pain episodes requiring hospitalization is unknown. 20 In the current 16-week trial, sildenafil therapy did not improve exercise capacity nor did it decrease Doppler-defined estimated right ventricular systolic pressure, as had been suggested in previous nonrandomized, uncontrolled studies. It is possible that by increasing pain, sildenafil interfered with subjects' ability to perform the 6MW test, although post hoc analysis did not demonstrate a relationship between report of pain by Brief Pain Inventory and 6MW distance.…”
Section: Sildenafil In Patients With Elevated Trv 861supporting
confidence: 55%
See 2 more Smart Citations
“…on April 3, 2019. by guest www.bloodjournal.org From prevented or minimized the development of pain episodes requiring hospitalization is unknown. 20 In the current 16-week trial, sildenafil therapy did not improve exercise capacity nor did it decrease Doppler-defined estimated right ventricular systolic pressure, as had been suggested in previous nonrandomized, uncontrolled studies. It is possible that by increasing pain, sildenafil interfered with subjects' ability to perform the 6MW test, although post hoc analysis did not demonstrate a relationship between report of pain by Brief Pain Inventory and 6MW distance.…”
Section: Sildenafil In Patients With Elevated Trv 861supporting
confidence: 55%
“…This observation of an increased rate of subjects experiencing serious SCD pain episodes was not reported previously in 2 open-label studies, most likely due to the absence of control groups or to differences in patient selection. 19,20 In one of the prior studies, subjects underwent maximization of SCD specific therapy with hydroxyurea and/or red blood cell transfusions before initiation of sildenafil. Whether this *Statistics for the 6MWD test were based on an ANCOVA model with treatment as a fixed effect and baseline 6MWD distance, TRV stratum, and study site as covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO exerts its vascular effects principally by binding and activating soluble guanylyl cyclase, boosting intracellular cyclic guanosine monophosphate (cGMP) levels (87,88). In pulmonary vasculature, this is counterbalanced by the phosphodiesterase-5 (PDE-5) enzyme, which hydrolyzes cGMP.…”
Section: Management and Specific Therapy For Scd-associated Pulmonarymentioning
confidence: 99%
“…81 Certain agents that reduce production of ROS, 81 such as xanthine oxidase, or others that reduce cell-endothelium adhesion, may be of benefit. Sildenafil amplifies the response of vascular musculature to NO and is being used in clinical trials for the treatment of pulmonary hypertension in SCA, 82 but the greatest concern related to the use of this type of medication is the possibility of male patients developing priapism. Recently, Canalli et al demonstrated that in vitro adhesion of neutrophils to fibronectin and the ICAM-1 protein, which is increased in SCD, is significantly reduced in the presence of pharmacological NO donation agents, such us sodium nitroprusside and diethylamine NONOate (DEANO).…”
Section: S43mentioning
confidence: 99%